Study guides

☆☆

Q: What is 11 2 - 5 6?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

(5/6) * (1/10) + (2/3) / (4/11) = (5/6) * (1/10) + (2/3) * (11/4)= (1/12) + (11/6) = 1/12 + 22/12 = 23/12 or 111/12(5/6) * (1/10) + (2/3) / (4/11) = (5/6) * (1/10) + (2/3) * (11/4)= (1/12) + (11/6) = 1/12 + 22/12 = 23/12 or 111/12(5/6) * (1/10) + (2/3) / (4/11) = (5/6) * (1/10) + (2/3) * (11/4)= (1/12) + (11/6) = 1/12 + 22/12 = 23/12 or 111/12(5/6) * (1/10) + (2/3) / (4/11) = (5/6) * (1/10) + (2/3) * (11/4)= (1/12) + (11/6) = 1/12 + 22/12 = 23/12 or 111/12

5 / 6 * 14 = 70 / 6 = 11 4 / 6 = 11 2 / 3

5 + 6 = 11 6 + 5 = 11 11 - 6 = 5 11 - 5 = 6

the patter is -2 +3 -4 +5 -6 +7 so it goes 8 6 9 5 10 4 11 3 12 2 11 1 10

11*sqrt(8) + 6*sqrt(12) - 5*sqrt(2) = 11*sqrt(4*2) + 6*sqrt(4*3) - 5*sqrt(2) = 11*sqrt(4)*sqrt(2) + 6*sqrt(4)*sqrt(3) - 5*sqrt(2) = 11*2*sqrt(2) + 6*2*sqrt(3) - 5*sqrt(2) = 22*sqrt(2) - 5*sqrt(2) + 12*sqrt(3) = 17*sqrt(2) + 12*sqrt(3) and that cannot be simplified further.

Related questions

Multiplication is simply repetitive addition. For instance, the expanded form of 2 * 3 is: 2 + 2 + 2, or 3 + 3. The expanded form of 5 * 6 is: 5 + 5 + 5 + 5 + 5 + 5, or 6 + 6 + 6 + 6 + 6. From the information above, it is evident that 11 * 5 = 11 + 11 + 11 + 11 + 11, and 11 * 6 = (11 * 5) + 11 So, substitute 55 for 11 * 5: 11 * 6 = 55 + 11 11 * 6 = 66

6 + 2K = 11 subtract 6 from each side - 6 + 6 + 2K = 11 - 6 2K = 5 divide the integers both sides by 2 K = 5/2 check 6 + 2(5/2) = 11 6 + 10/2 = 11 6 + 5 = 11 11 = 11 checks

2*3=6 11-6=5 so the answer is 5

1/2 x + 6 = 11 1/2 x + 6 - 6 = 11 - 6 1/2 x = 5 2*(1/2 x) = 5*2 x = 10 1/2 of 10 is 5, 5 plus 6 is 11 QED

-11

2 minus 5/6 = 11/6

2/3 x 2/2 = 4/6 7/6 + 4/6 = 11/6 11 = 6 + 5 Answer: 11/6 or 1 and 5/6

they are called fact families if you just need an example: 5+6=11 6+5=11 11-5=6 11-6=5

2/5/11 or 2/6/11

8*(5+11)/(2+6)= 8(16)/8= 16

a=6,b=5 a=a+b;/*11*/ b=a-b;/*11-5=6*/ a=a-b;/*11-6=5*/

1

People also asked